2005
DOI: 10.1002/marc.200500085
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleating Effect of Carbon Nanotubes on Crystallinity in R‐BAPB‐Type Thermoplastic Polyimide

Abstract: Summary: The relatively high degree of crystallinity of a new thermoplastic polyimide (PI) makes it a favorable matrix candidate for fiber reinforced composites. This advantage is the result of the ability of the matrix to recrystallize during the composite manufacturing process. In this study we examine the potential nucleating effect of carbon nanotubes on a thermoplastic PI. In addition to their inherent mechanical contribution, the carbon nanotubes help recover a significant proportion of the original crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 14 publications
6
43
0
Order By: Relevance
“…It is no surprise then that carbon nanotubes (CNTs) have also been shown to nucleate crystal growth in long chain polymers. [18,19] To date, CNT nucleated crystallization as well as templated and ordered crystallization of macromolecules has been observed and studied for a number of polymers. Due to its rod-like structure and axial alignment of the graphite plane, epitaxial crystallization between CNT and polymers is one potential route for producing composite fibers with enhanced interfacial interaction, extended-chain polymer morphology, and resultant highstrength and modulus.…”
Section: Introductionmentioning
confidence: 99%
“…It is no surprise then that carbon nanotubes (CNTs) have also been shown to nucleate crystal growth in long chain polymers. [18,19] To date, CNT nucleated crystallization as well as templated and ordered crystallization of macromolecules has been observed and studied for a number of polymers. Due to its rod-like structure and axial alignment of the graphite plane, epitaxial crystallization between CNT and polymers is one potential route for producing composite fibers with enhanced interfacial interaction, extended-chain polymer morphology, and resultant highstrength and modulus.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that MWCNT accelerated the crystallization in a certain type of polypropyrene and polyimide. 17,18 When MWCNT were entangled one another as lump, the entangled points might T. TAKAHASHI et al…”
Section: Effect Of Carbon Materials On Induced Crystallizationmentioning
confidence: 99%
“…Dynamic melt rheological property as a function of time suggested the increase of storage and loss moduli around 200 C. It was reported that MWCNT also crystallizes a certain type of thermoplastic polyimide and polypropyrene. 17,18 However, little is known about the cause and the structure of induced crystallization by VGCF or MWCNT. Here, the effect of pre-graphitized VGCF, carbon black, and mesophase pitch based carbon fiber (CF) on the crystallization was examined.…”
mentioning
confidence: 99%
“…The crystallization of the R-ODFO matrix after melting can be accelerated by modifying it with bis-imides of chemical structure similar to that of the PI itself, which is explained by the plastification effect, which increases the molecular mobility of the PI and correspondingly the capacity to crystallize [5][6][7] We have researched the effects of carbon fillers of nanodimensional level on the mechanical properties of CP based on PI in the R-ODFO matrix crystallization [8][9][10]. Those particles act as nuclei for the crystallization of the polymer matrix, for which we have selected carbon nanofibers obtained by pyrolytic deposition of carbon (VGCF, Showa Denko company, Japan).…”
mentioning
confidence: 99%
“…For some years [5][6][7][8][9][10] we have been researching thermoplastic PI based on 1,3-bis-(3,3′,4,4′-dicarboxyphenoxy)benzene (R) and 4,4′-bis-(4-aminophenoxy)disphenyl (ODFO) for use as binders for carbon plastics:…”
mentioning
confidence: 99%